SISTEM HIDROLIK LOADING UNLOADING MEJA PELUNCUR - Warsianto, Ardi; F. Alqap, A. Sofwan; zuliantoni; Hardiyanto, Martin (UNIB Press, 2024)
Mortars have been developed in the field of weapons. One of the developments is the installation of a mortar on the rear of the vehicle platform which is equipped with a navigation system and combined with a computerized fire control system. To support this, a hydraulic system is needed. A hydraulic system is a form of changing or transferring power by using a conducting medium in the form of a liquid fluid to obtain greater power than the initial power released. The purpose of this practical work report is to find out how the hydraulic system works and find out the components used in the hydraulic system for loading and unloading mortar panzers. This research process starts from literature study, field observations, topic determination, data collection, results and discussion, conclusions. Based on this research, the results showed that the way the hydraulic system works, starts from the electric motor which turns on the pump, then the pump sucks the fluid in the tank, after that a fluid flow pressure is produced which then flows towards the valve, the valve will control the direction and pressure, fluid flow rate through the flexible pipe house to the working cylinder. Meanwhile, the components that make up the hydraulic system used are an electric motor with a speed of 1420 rpm, a pump with a power of 12 W and max. pressure 250 bar, manual pump, valve with max. operating pressure 210 bar and max. flow rate 63-100 L/min, flexible house pipe, fluid, pressure gauge, tank with a volume of 50 liters, filter, double acting hydraulic cylinder type accuator.